Noxious weed monitoring at the U.S. Air Force Academy: year 11 results - Smith, Pam, author; Rondeau, Renée, author; Greenwell, Amy, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2016)
This report includes a summary of the results of the past eleven years of population monitoring of targeted noxious weeds at the U.S. Air force Academy ("the Academy"), emphasizing changes that were observed between 2012 and 2015.
Prepared for: U.S. Air force Academy Department of Natural Resources.
May 2016.
Keywords: Colorado; noxious weeds; weed control; vegetation surveys